Microencapsulated healing agents for an elevated-temperature cured epoxy: influence of viscosity on healing efficiency - Ghazali, Habibah (SAGE Publications Ltd, 2021)
Among many applications, elevated-temperature cured epoxy resins are widely used for high-performance applications especially for structural adhesive and as a matrix for structural composites. This is due to their superior chemical and mechanical properties. The thermosetting nature of epoxy produces a highly cross-linked polymer network during the curing process where the resulting material exhibited excellent properties. However, due to this cross-linked molecular structure, epoxies are also known to be brittle, and once a crack initiated in the material, it is difficult to arrest the crack propagation. Earlier research found that the inclusion of encapsulated healing agents is able to introduce self-healing ability to the room-temperature cured epoxies. The current study investigated the self-healing behaviour of an elevated-temperature cured epoxy, which incorporated the dual-capsule system loaded with diglycidyl-ether of bisphenol-A (DGEBA) resin and mercaptan. The microcapsules were prepared by the in-situ polymerisation method while the fracture toughness and the self-healing capability of the tapered-double-cantilever-beam (TDCB) epoxy specimens were measured under Mode-I fracture toughness testing. We investigated the effect of temperature on viscosity of the healing agents and how these values influence the formation of uniform healing on the fracture surfaces. It was found that incorporation of the dual-capsule self-healing system onto an elevated-temperature cured epoxy slightly changed the fracture toughness of the epoxy as indicated by the Mode-I testing. In the case of thermal healing at 70°C, the self-healing epoxy exhibited a recovery of up to 111% of its original fracture toughness, where a uniform spreading of the healant was observed. The excellent healing behaviour is attributed to the lower viscosity of the healant at higher temperature and the higher glass transition temperature (Tg) of the produced healant film. The DSC analysis confirmed that the healing process was not contributed by the post-curing of the host epoxy.